15 Ways to Support Young Children and Their Families in the COVID-19 Response - World Bank (World Bank, Washington, DC, 2020)
As the global COVID-19 (Coronavirus) pandemic continues to unfold, young children will be especially vulnerable. World Bank teams can work with client countries to support early childhood development (ECD) by leveraging a range of interventions and mechanisms that will be part of the COVID-19 (Coronavirus) response in every country. The report has three key messages : The early years are a critical period to build human capital. Young children are disproportionately at risk and must be prioritized in COVID-19 (Coronavirus) responses. We will reach young children by supporting parents and caregivers.